Excursion – The Opportunity of Combining the Theory with the Practice - Saida Adilovna, Nizamova (International Journal of Psychosocial Rehabilitation, 2020)
The article provides information on the use of excursion methods and forms, tools, and tools for the development of science on the part of children with disabilities.